Symptomatic lumbosacral perineural cysts: A report of three cases and review of literature - Sharma, Mayur; Velho, Vernon; Mally, Rahul; Khan, Shadma (Asian Journal of Neurosurgery, 2015)
Lumbosacral perineural cysts (Tarlov’s cysts) are nerve root cysts, which are usually asymptomatic and are detected incidentally on imaging. These cysts are rare with an incidence of 4.6%. We report three cases of Lumbosacral Tarlov’s cysts, which presented with cauda equina syndrome and radicular pain syndrome. Two of our patients had symptoms of cauda equina syndrome, and one had acute sciatica. Complete excision of the cyst was achieved in two patients and marsupialization of the cyst was done in another patient due to its large size and dense adherence to the sacral nerve roots. All the patients were relieved of the radicular pain with no new neurological deficit following surgery. Symptomatic lumbosacral Tarlov’s cyst is a rare lesion, and the presentation can be low back pain, cauda equina syndrome or sciatica. Therefore, this entity should be kept in the differential diagnosis of patients presenting with these symptoms. Complete Surgical excision of these symptomatic cysts is the treatment of choice to achieve a cure.
Keywords: cyst; lumbosacral; perineural; symptomatic